Digital Terrain Modelling Development and Applications in a Policy Support Environment - Peckham, Robert Joseph; Jordan, Gyozo (Lecture Notes in Geoinformation and Cartography, 2007)
This book presents a set of papers on Digital Terrain Modelling for Policy Support which aims to be informative and stimulating for both developers and users of digital terrain models. It should also be useful for professi- als who are interested in the wider aspects of the applications of terrain models in support for policies and decision making. There is an increasing demand for regional and continental scale data for use in environmental modelling and spatial analysis to support envir- mental policy development and implementation. Important environmental processes act at regional and continental scales, for example climatic change inducing floods and soil erosion, and management of these pr- esses for the sustainable development of society requires policies to be - plied at the corresponding scales. One of the most important factors inf- encing these environmental processes which act on the earth's surface is the surface topography, hence the need for extensive, harmonised digital terrain models.